A SYNOPSIS OF THE SUBTRIBE BAMBUSINAE (GRAMINEAE: BAMBUSOIDEAE) IN VIETNAM - Trần Văn Tiến (Tạp chí Khoa học Đại học Đà Lạt, 2017)
A complete list of accepted names for the Vietnam Subtribe Bambusinae Presl comprises 11 genuses, which are widely distributed in tropical and subtropical region in Vietnam, from commonest bamboos grown around villages to forests. It is distinguished from the closely related subtribe by having rhizomes sympodial; tree, shrub or scrambler; branch complement several, 1 dominat; inflorescence iterauctant.